Repatriates: the relationship between bicultural self-efficacy and repatriate difficulty - Aure, Aaron, author (Colorado State University. Libraries, 2003)
The study hypothesized a positive influence of bicultural competencies (BC) -- specifically bicultural self-efficacy (BSE) -- on repatriate difficulties (RD) and possible group differences between minority and dominant groups. One hundred and thirty-two students returning from a study abroad experience were used as participants. Students were solicited using e-mail and asked to complete a web survey. The survey consisted of two scales measuring BSE and RD. The survey also collected categorical data including sex, ethnicity, terms spent abroad, terms since return, and fluency in the host country language. The BSE scale (α = .73) was an adapted scale from (Harrison, 1996), and the RD scale (α = . 79) was created from eight RD themes (Osland, 2000). A factor analysis on the RD items resulted in two separate factors, Host Country Comparisons (HCC) and Home Country Specifics (HCS). HCC had an overarching theme of comparing host country experiences with home country experiences. The questions related to HCS had an overarching theme related to RD experiences specific to the context of the home country. A small to medium size positive correlation was found between BSE and one aspect of repatriate difficulty, HCC (p = .005). Statistical significance was not found between the minority and dominant groups. Also, no group differences were found after controlling for categorical variables. The study suggested that BCs have a positive relationship with RD. To further understand these results a post-hoc literature review was completed on five other Bicultural Competencies, which resulted in continued support of the study's hypotheses. Further research will be required to provide additional empirical evidence to either refute or support these initial findings. This study concluded that: (1) BSE and BCs may have a positive relationship with RD. (2) The theory supporting this study might not be accurate, although one study is not adequate to refute such theories. (3) The impact of one BC may not be adequate to provide a clear positive or negative relationship with RD. Including the other 5 Bicultural Competencies may not only show a clear relationship with RD but also help us further understand the concept of BCs.
Covers not scanned.
Keywords: Self-efficacy; Repatriation; Biculturalism